Catheter ablation of ventricular tachycardia in patients with prior cardiac surgery: An analysis from the International VT Ablation Center Collaborative Group. (24th January 2021) - Aguilar, Martin; Tedrow, Usha B.; Tzou, Wendy S.; Tung, Roderick; Frankel, David S.; Santangeli, Pasquale; Vaseghi, Marmar; Bunch, T. Jared; Di Biase, Luigi; Tholakanahalli, Venkatakrishna N.; Lakkireddy, Dhanunjaya; Dickfeld, Timm; et al.
Abstract: Introduction: Patients with prior cardiac surgery may represent a subgroup of patients with ventricular tachycardia (VT) that may be more difficult to control with catheter ablation. Methods: We evaluated 1901 patients with ischemic and nonischemic cardiomyopathy who underwent VT ablation at 12 centers. Clinical characteristics and VT radiofrequency ablation procedural outcomes were assessed and compared between those with and without prior cardiac surgery. Kaplan–Meier analysis was used to estimate freedom from recurrent VT and survival. Results: There were 578 subjects (30.4%) with prior cardiac surgery identified in the cohort. Those with prior cardiac surgery were older (66.4 ± 11.0 years vs. 60.5 ± 13.9 years, p < .01), with lower left ventricular ejection fraction (30.2 ± 11.5% vs. 34.8 ± 13.6%, p < .01) and more ischemic heart disease (82.5% vs. 39.3%, p < .01) but less likely to undergo epicardial mapping or ablation (9.0% vs. 38.1%, p <.01) compared to those without prior surgery. When epicardial mapping was performed, a significantly greater proportion required surgical intervention for access (19/52 [36.5%] vs. 14/504 [2.8%]; p < .01). Procedural complications, including epicardial access‐related complications, were lower (5.7% vs. 7.0%, p < .01) in patients with versus without prior cardiac surgery. VT‐free survival (75.1% vs. 74.1%, p = .805) and survival (86.5% vs. 87.9%, p = .397) were not different between those with and without prior heart surgery, regardless of etiology of cardiomyopathy. VT recurrence was associated with increased mortality in patients with and without prior cardiac surgery. Conclusion: Despite different clinical characteristics and fewer epicardial procedures, the safety and efficacy of VT ablation in patients with prior cardiac surgery is similar to others in this cohort. The incremental yield of epicardial mapping in predominant ischemic cardiomyopathy population prior heart surgery may be low but appears safe in experienced centers.